Millennial Farmer Program Analysis at the North Sumatra Plantation Office - Elda Anzeli Hasibuan; Annio Indah Lestari Nasution (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Agriculture is one of the important sectors in the Indonesian economy. Although agriculture plays an important role in Indonesia's economic sector, in the era of rapid modernization, the development of this field still seems to be less effective in utilizing various technologies. However, the number of officials in the agricultural and plantation sectors who are authorized to formulate technical policies, implement policies, conduct assessments and reporting, and manage agriculture and plantations is not proportional to the breadth of distribution in the agricultural sector. in Indonesia. Therefore, the role of farmers and the community is to participate in assisting the Ministry of Agriculture and Plantations in fulfilling their responsibilities and authorities. However, currently there is no application that can really help farmers cultivate their land. From the actual situation in the field, many farmers are still using traditional methods, so agricultural productivity is slow. The presence of millennial farmers offers another option to accelerate farmer regeneration. Millennial farmers are seen as able to connect young farmers with long-term farmers. However, the trend in the field has not seen the special characteristics of millennial farmers. This study aims to describe the main characteristics of millennial farmers and analyze the factors that influence the personality formation of millennial farmers. Factors that have a significant positive effect on the personality formation of millennial farmers are personal characteristics, technical abilities and managerial abilities, while social skills have a negative effect.